Interference of CD40L-Mediated Tumor Immunotherapy by Oncolytic Vesicular Stomatitis Virus - Galivo, Feorillo (Mary Ann Liebert, Inc., 2010)
Oncolytic virotherapy can be achieved in two ways: (1) by exploiting an innate ability of certain viruses to selectively replicate in tumor tissues, and (2) by using viruses to deliver toxic or immunostimulatory genes to tumors. Vesicular stomatitis virus (VSV) selectively replicates in tumors lacking adequate type I interferon response. The efficacy of oncolytic virotherapy using VSV against B16 melanomas in C57BL/6 mice is dependent on CD8(+) T and natural killer cells. Because immunotherapies that prime specific CD8(+) T cells against melanocyte/melanoma antigens can generate significant therapeutic responses, we hypothesized that engineering VSV to express the potent T cell costimulatory molecule CD40 ligand (VSV-CD40L) would enhance virotherapy with concomitant priming of melanoma-specific T cells. However, we observed no difference in antitumor efficacy between the parental VSV-GFP and VSV-CD40L. In contrast, intratumoral injection of a replication-defective adenovirus expressing CD40L (Ad-CD40L) consistently produced significantly greater therapy than either replication-competent VSV-GFP or VSV-CD40L. The Ad-CD40L-mediated tumor regressions were associated with specific T cell responses against tumor-associated antigens (TAAs), which took several days to develop, whereas VSV-CD40L rapidly induced high levels of T cell activation without specificity for TAAs. These data suggest that the high levels of VSV-associated immunogenicity distracted immune responses away from priming of tumor-specific T cells, even in the presence of potent costimulatory signals. In contrast, a replication-defective Ad-CD40L allowed significant priming of T cells directed against TAAs. These observations suggest that an efficiently primed antitumor T cell response can produce similar, if not better, therapy against an established melanoma compared with intratumoral injection of a replication-competent oncolytic virus.